MEDB-41. Identifying a subgroup of patients with early childhood sonic hedgehog-activated medulloblastoma with unfavorable prognosis after treatment with radiation-sparing regimens including intraventricular methotrexate. (3rd June 2022) - Tonn, Svenja; Obrecht, Denise; Sill, Martin; Spohn, Michael; Milde, Till; Pietsch, Torsten; Bison, Brigitte; Juhnke, Björn-Ole; Struve, Nina; Friedrich, Carsten; von Bueren, André O; Gerber, Nicolas U; et al.
Abstract: PURPOSE/METHODS: Clinical and molecular risk factors in 142 patients <5 years with desmoplastic medulloblastoma (DMB) or medulloblastoma with extensive nodularity (MBEN) were investigated. Patients were diagnosed between 1992 and 2020 and treated with radiation-sparing approaches, 131 with intraventricular methotrexate. 14 patients with metastatic disease received high-dose chemotherapy. DNA methylation profiles of 77 sonic hedgehog (SHH)-activated medulloblastoma were reclassified according to the Heidelberg Brain Tumor Classifier Version 12.3. RESULTS: While metastatic disease or incomplete resection did not impact progression-free survival (PFS) and overall survival (OS), patients with MBEN had superior outcomes to DMB (5-year PFS 93% vs 71%, p=0.004; 5-year OS 100% vs 90%, p=0.026). Older patients had less favorable PFS (5-year PFS [>3 years] 47% vs 85% [<1 year] vs 84% [1-3 years], p<0.001). No TP53 mutations were detected (n=47). DNA methylation classification identified three subgroups: SHH-1v12.3 (n=39), SHH-2v12.3 (n=19), and SHH-3v12.3 (n=19), with distinct cytogenetic profiles (chromosome 2 gains in SHH-1v12.3, very few alterations in SHH-2v12.3, and chromosome 9q losses in SHH-3v12.3 ), age profiles (median age [years] SHH-1v12.3 : 1.7, SHH-2v12.3 : 0.9, SHH-3v12.3 : 3.0, p<0.001), and histological distribution (SHH-2v12.3 : 74% MBEN, SHH-1v12.3 /SHH-3v12.3 : 77%/79% DMB, p<0.001). PFS was more unfavorable in patients with SHH-3v12.3 -medulloblastoma (5-year PFS 53% vs 86% [SHH-1v12.3 ] vs 95% [SHH-2v12.3 ], p=0.002), which remained the only risk factor on multivariable Cox regression for PFS. OS was comparable (5-year OS 94% [SHH-3v12.3 ] vs 97% [SHH-1v12.3 ] vs 100% [SHH-2v12.3 ], p=0.6). 8/9 patients with SHH-3v12.3 -medulloblastoma received radiotherapy at relapse (6 craniospinal, 2 local [1 Gorlin syndrome, 1 BRCA2 germline mutation], 1 no radiotherapy [Gorlin syndrome]). CONCLUSION: We identify patients with an increased risk of relapse when treated with radiation-sparing approaches among children with early childhood SHH-medulloblastoma. If these tumors differ from SHH-3-medulloblastoma typically described in older children remains to be verified. Treatment recommendations need to consider cancer predisposition syndromes.